2003
DOI: 10.1152/jn.00900.2002
|View full text |Cite
|
Sign up to set email alerts
|

A Temporally Asymmetric Hebbian Rule Governing Plasticity in the Human Motor Cortex

Abstract: Classen. A temporally asymmetric Hebbian rule governing plasticity in the human motor cortex. J Neurophysiol 89: 2339 -2345, 2003. First published January 22, 2003 10.1152/jn.00900.2002 Synaptic plasticity is conspicuously dependent on the temporal order of the pre-and postsynaptic activity. Human motor cortical excitability can be increased by a paired associative stimulation (PAS) protocol. Here we show that it can also be decreased by minimally changing the interval between the two associative stimuli. Cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
533
3
8

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 522 publications
(601 citation statements)
references
References 54 publications
40
533
3
8
Order By: Relevance
“…As a consequence, the LTP-like increase in MEP amplitude of 1.71 ± 0.05 in the PBO condition is one of the largest reported in the literature (Wolters et al, 2003;Stefan et al, 2004;Ziemann et al, 2004;Nitsche et al, 2007). Therefore, one might argue that LTP-like plasticity was saturated already under PBO conditions and could not be enhanced any further.…”
Section: Neuromodulatory Drugs and Ltp-like Plasticitymentioning
confidence: 86%
“…As a consequence, the LTP-like increase in MEP amplitude of 1.71 ± 0.05 in the PBO condition is one of the largest reported in the literature (Wolters et al, 2003;Stefan et al, 2004;Ziemann et al, 2004;Nitsche et al, 2007). Therefore, one might argue that LTP-like plasticity was saturated already under PBO conditions and could not be enhanced any further.…”
Section: Neuromodulatory Drugs and Ltp-like Plasticitymentioning
confidence: 86%
“…After-effects of tDCS and PAS are NMDA-and Ca 2 þ -dependent (Nitsche et al, 2003a;Stefan et al, 2002;Wolters et al, 2003). It has been shown that serotonin facilitates NMDA receptor-dependent LTP (Park et al, 2012).…”
Section: Proposed Mechanisms Of Actionmentioning
confidence: 99%
“…Citalopram enhanced facilitatory plasticity induced by anodal tDCS and converted cathodal tDCS-induced inhibitory plasticity into facilitation . tDCS and paired associative stimulation (PAS) are non-invasive brain stimulation techniques inducing changes in cortical excitability that outlast the stimulation duration (Nitsche et al, 2003b;Paulus, 2000, 2001;Stefan et al, 2000;Wolters et al, 2003). These alterations in cortical excitability are NMDA-and Ca 2 þ -dependent (Nitsche et al, 2003a;Stefan et al, 2002;Wolters et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the systems level of human M1, LTP-like plasticity, indexed by a long-term increase in motor-evoked potential (MEP) amplitude, can be induced by paired associative stimulation (PAS LTP ) (Cooke and Bliss, 2006;Müller-Dahlhaus et al, 2010;Stefan et al, 2002;Stefan et al, 2000;Ziemann et al, 2004). This LTP-like increase in MEP amplitude shows tight similarities to cellular LTP because it is associative, input specific, and blocked by dextromethorphan, a non-competitive NMDAR antagonist (Stefan et al, 2002;Stefan et al, 2000;Wolters et al, 2003). Furthermore, PAS LTP -induced LTP-like plasticity interacts homeostatically with prior or subsequent motor learning (Elahi et al, 2013;Jung and Ziemann, 2009;Kang et al, 2011;Rosenkranz et al, 2007;Stefan et al, 2006;Ziemann et al, 2004), indicating its mechanistic importance in learning processes.…”
Section: Introductionmentioning
confidence: 99%